1962
DOI: 10.1037/h0047739
|View full text |Cite
|
Sign up to set email alerts
|

Early experiences and occupational choice: A test of Roe's hypothesis.

Abstract: One recent theory which seeks to deal with factors related to occupational choice is that of Roe (1956;1957). Roe's theory evolved from the concept of the close relationship between an individual's interests and needs and his occupation, and the 1 relationship between early life experiences and the development of these interests and needs. According to the theory the parents create a particular psychological climate by the manner in which they satisfy or frustrate the early needs of the child. As a result, a b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1963
1963
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 2 publications
(2 reference statements)
1
13
0
Order By: Relevance
“…Roe (1957) hypothesized that people who were brought up in a family atmosphere that was warm, attentive (if not overprotective), and child-centered, would prefer social service vocations, whereas those brought up in a cold, non-child-oriented family would prefer non-person-type vocations (e.g., science or technology). Although not all the research confirms Roe's hypothesis (e.g., Grigg, 1959;Switzer, Grigg, Miller, & Young, 1962), some research does (e.g., Hagen, 1960;Utton, 1962). Nachmann (1960) found that lawyers and dentists tend to have a father-dominated, impulse-repressing family, whereas those in social work tend to come from mother-dominated, impulse-channeling families, families in which the children are taught concern for human suffering.…”
Section: Cognitive Abilitiesmentioning
confidence: 91%
“…Roe (1957) hypothesized that people who were brought up in a family atmosphere that was warm, attentive (if not overprotective), and child-centered, would prefer social service vocations, whereas those brought up in a cold, non-child-oriented family would prefer non-person-type vocations (e.g., science or technology). Although not all the research confirms Roe's hypothesis (e.g., Grigg, 1959;Switzer, Grigg, Miller, & Young, 1962), some research does (e.g., Hagen, 1960;Utton, 1962). Nachmann (1960) found that lawyers and dentists tend to have a father-dominated, impulse-repressing family, whereas those in social work tend to come from mother-dominated, impulse-channeling families, families in which the children are taught concern for human suffering.…”
Section: Cognitive Abilitiesmentioning
confidence: 91%
“…These orientations were hypothesized to lead to specific career clusters; for example, careers in the arts were thought to derive from an overprotecting parenting style, science careers from parental rejection, and technological careers from casual acceptance. A number of studies tested these hypotheses with no success (Grigg, 1959;Hagen, 1960;Switzer, Grigg, Miller, & Young 1962;Utton, 1962). In 1964, Roe abandoned most of her specific hypotheses and suggested that person-oriented occupations are selected more often by children with secure attachments in their early experiences.…”
mentioning
confidence: 99%
“…This paper stimulated a series of presumed tests of the "Roe hypothesis" (66,70,171,184); th e findings were essentially negative. Th e differentiatio n stems largely from th e early work of Roe on th e personality characteristics distinguishing scientists from nonscientists.…”
Section: Vocational Behavior-theories and Findingsmentioning
confidence: 92%